Cost-Effectiveness of First-Line Atezolizumab versus Chemotherapy in Non-Small-Cell Lung Cancer Patients Ineligible for Platinum-Containing Regimens - Li LF; Qi R; Wei TT; Feng L; Zhang X; Liu Q (Dove Medical Press, 2024)
Lan-Fang Li,1 Ran Qi,1 Tian-Tian Wei,1 Lei Feng,1 Xin Zhang,1 Qiao Liu2 1Department of Clinical Pharmacy, Affiliated Hospital of Jining Medical University, Jining Medical University, Jining, Shandong, 272029, People's Republic of China; 2Department of Pharmacy, The Second Xiangya Hospital of Central South University, Changsha, Hunan, 410011, People's Republic of ChinaCorrespondence: Qiao Liu, Department of Pharmacy, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People's Republic of China, Email liuqiao6767@csu.edu.cnPurpose: The IPSOS study provided evidence supporting the efficacy and tolerability of first-line atezolizumab compared to single-agent chemotherapy for non-small-cell lung cancer (NSCLC) patients ineligible for treatment with a platinum-containing regimen. This study aimed to assess the cost-effectiveness of atezolizumab specifically in this population, considering the perspective of the Chinese healthcare system.Patients and Methods: In this analysis, a three-state Markov model was utilized. The survival data were derived from the IPSOS clinical trial. Direct medical costs and utility values were collected from national authoritative database and published literature. The primary outcomes were costs, quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratio (ICER). To ensure the robustness of our model, both one-way and probabilistic sensitivity analyses were conducted.Results: Atezolizumab monotherapy led to an increase in costs of $4139.23 compared to single-agent chemotherapy. Additionally, it resulted in a gain of 0.14 QALYs, leading to an ICER of $29,365.79 per QALY, which was below the willingness-to-pay threshold of $36,066 per QALY used in the model. One-way sensitivity analyses revealed cost of atezolizumab and utility of progressive disease (PD) as major influencing factors for ICER. Furthermore, probabilistic sensitivity analyses confirmed our base-case results.Conclusion: From the perspective of the Chinese healthcare system, atezolizumab emerges as a cost-effective choice for the first-line treatment of NSCLC patients ineligible for platinum-based chemotherapy.Keywords: atezolizumab, cost-effectiveness, NSCLC, IPSOS